2022
DOI: 10.1021/acssuschemeng.2c03755
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Myrcene in Both Conventional and Renewable Solvents: Postpolymerization Modification via Regioselective Photoinduced Thiol–Ene Chemistry for Use as Carbon Renewable Dispersants

Abstract: Polymeric dispersants are useful materials used in many different industries and often derived from oil-based chemicals, for example, in automotive fluids so as to prevent particulates from precipitation and causing potential damage. These are very often polyisobutene derivatives, and there is a growing need to replace these using chemicals using renewable resources such as the use of naturally occurring myrcene. Polymyrcene (PMy), with an ordered microstructure, has been successfully synthesized via both anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…This results in a significant variation of the V/V percentage of hexanes in the reaction medium (hexanes/THF): 14% (batch) and 29% (flow) with obvious consequences on the reactivity and selectivity. 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a significant variation of the V/V percentage of hexanes in the reaction medium (hexanes/THF): 14% (batch) and 29% (flow) with obvious consequences on the reactivity and selectivity. 42…”
Section: Resultsmentioning
confidence: 99%
“…This results in a significant variation of the V/V percentage of hexanes in the reaction medium (hexanes/THF): 14% (batch) and 29% (flow) with obvious consequences on the reactivity and selectivity. 42 The influence of the residence time t R was further evaluated at both of these temperatures from t R = 19 to 600 s by modifying the flow rates in a fixed length reactor (L = 0.5 m; entries 1-6, Table 3). As expected, the molar mass increased according to t R as well as to the temperature.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…Recently, many other research groups have shown tremendous interest in the anionic polymerization of terpenes and the postpolymerization reactions of these polymers (hydrogenation, epoxidation, etc. ). Furthermore, major contributions on the synthesis and study of terpene-based linear and branched macromolecular architectures have been reported by Frey’s group. , They have synthesized via anionic polymerization, several combinations of linear and complex macromolecular architectures of terpene-based copolymers (linear copolymers with PS, graft copolymers, polymerization of functionalized terpenes, etc.) (Figure ).…”
Section: Current Status Of Living Carbanionic Polymerizationmentioning
confidence: 99%
“…Similar to myrcene and farnesene structures, the presence of an additional double bond can offer a benefit over the vastly used nonfunctionalized isoprene- and butadiene-based materials. , Functionalization via several routes like thiol–ene “click” chemistry, epoxidation, hydrosilylation, etc. can be carried out on either the monomers or introduced via postpolymerization modifications to synthesize functional polymers. ,, …”
Section: Introductionmentioning
confidence: 99%